Simulação de Movimento de Robôs num Ambiente Cooperativo de Futebol - França, ícaro dos Santos (2001)
The present thesis is the first work on Mobile Autonomous Robots done at UFF to foster AI and Autonomous Mobile Robots research proceedings about movement trajectories in a randomical environment and a resume of the adopted proceedings on these subject. At examing a standard problem where a wide range of technologies can be integrated and organized (navigation systems, machine vision, AI algorithms and so on)that is described by the main paradigms as the system developped by The Escola Politécnica de São Paulo for the soccer robot team called GUARANÁ , which follows up the competition rules of the korean MIROSOT.